The Effect of Exercise Methods on Variations and Strengths of Explosive Muscle Power of The Power of 100 meters of Running Capability in State Middle School 1 Rambah Rokan Hulu Regency - Mulyadi, Hendri; Indah, Debby (Journal of Education, Health and Sport, 2019)
The problems found in male students of class VIII2 of SMP Negeri I Rambah Rokan Hulu District. that the results of the sprint run achieved by students are still not optimal, this is because the practice of watching too much does not make students take it seriously. Students are lazy, students are bored, students are stiff. From the students 'running techniques such as swinging their hands with foot movements less harmoniously, besides the coordination of the students' running movements were not maximal, so that when students ran, the coordination between swinging hands and feet still looked stiff and made the student's running speed reduced, beside seen from the leg muscle strength that students have, so to create the maximum running speed results, students always have to practice the variation training method and the strength of the leg muscles. The aims of this study was to determine the effect of the variation training method, leg muscle strength on the results of the 100-meters sprint in class VIII2 of SMP Negeri I Rambah Rokan Hulu Regency, Indonesian Country.The type of research is Pseudo Experiment. The population is all male students of class VIII2 of SMP Negeri I Rambah, Rokan Hulu Regency with a population of 14 male students, with the sampling technique being total sampling or taking the entire population of male students of class VIII2 in SMP Negeri I Rambah, 14 people in Rokan Hulu Regency. The instrument used in this study was to measure leg muscle strength by using the leg dynamometer test and to measure the run of students a 100-meters run test was conducted.The results of the study and analysis of the data showed that (1) the form of training methods for the variation of limb explosive strength significantly affected the increase of 100 meters runner effect of 8.11, it can be concluded that there was influence of leg muscle strength on the results of 100 meter sprints in male students class VIII2 State Middle School I Rambah Rokan Hulu Regency (2) the form of exercise using the power of explosive limb muscle power has a significant effect on the ability of the 100 meters running 9.07 (3) there is a difference in the effect of variation training with the explosive strength of leg muscle 0.96.